Influence of growth regulators on the seed productivity of medicinal crops grown in the Krasnodar region - N. S. Tropina; R. R. Thaganov; V. R. Thaganov; N. I. Sidelnikov (Овощи России, 2023)
Medicinal plants and preparations thereof are widely used in the treatment and prevention of many diseases. The demand of the pharmaceutical industry for herbal medicinal raw materials is met by culturing these plants. Pharmaceutical factories can be fully supplied with medicinal raw materials both by expanding the area and by increasing the yield of cultivated crops, which is achieved by using high-quality seeds of promising varieties in the required amount. In recent years, in the conditions of the Western Ciscaucasia in the medicinal crop rotation of the North Caucasus branch of VILAR, studies have been conducted to study the possibility of increasing the seed productivity of Echinacea purpurea L., Сhamomilla recutita L., Plantago major L. and Salvia officinalis L., which occupy an important place in the modern range of medicines used in official and traditional medicine. To this end, experiments were laid on the complex test of humic fertilizers (Lignogumat, Normat L) with growth regulators (Zircon, Agat, Gibbersib) and chelated micro-fertilizers (Siliplant and Cytovit)As a result of the studies carried out on echinacea, an increase in the yield of seeds and an improvement in their quality was established on the Lignogumat + Agate variant (by 31%), and on sage and chamomile – Lignogumat + Zircon (by 28% and 39%, respectively), the weight of 1000 seeds exceeded the control by 8-15%. Non-root feeding of echinacea and plantain with Lignogumat and Normat L with silicon-containing microfertilization Siliplant ensured increase of seed productivity by 14-16%, mass of 100 seeds increased by 8-10%. Thus, by using complexes of humic preparations with growth regulators and silicon-containing microfertilization Siliplant as effective means of regulating the growth and development of medicinal cultures, activating flowering and seed formation processes, it is possible to ensure high yield and the best quality of the resulting seed material.